Marketing Strategy Of Smes For Durability On Covid Pandemic-19 Session - Supriono, Supriono; Sudarmiatin, Sudarmiatin; Hermawan, Agus (Publisher Cv. Inara, 2022)
The economy is one of the most important pillars in state activities, the wheels of the economy are run by various sectors and the MSME sector is a sector that has a major contribution to building the economy in Indonesia. As a result of the Covid-19 pandemic that entered Indonesia in early 2020 and spread rapidly to various regions and caused major disruptions to ongoing economic activities. One of the biggest impacts was felt by most MSMEs so they were forced to go out of business due to not being able to survive the difficult conditions during the Covid-19 pandemic. For this reason, researchers want to know the marketing strategy implemented by culinary tourism that has succeeded in maintaining the durability of its business during the Covid-19 pandemic. The type of research used in this study is qualitative research. This study uses 4 samples of MSMEs for culinary tourism in Malang, namely Depot Hok Lay Cwie Mie culinary tours, Mie Bakar Celaket culinary tours, Bakso President culinary tours and Seoulscents Korean Café culinary tours. The results of this study. The results of this study indicate that 4 MSMEs for culinary tourism in Malang City have their own ways of building and adjusting the 4P Mix Marketing marketing strategy in order to maintain the durability of their business during the Covid-19 pandemic.